1995
DOI: 10.1136/bjsm.29.3.147
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of methods of predicting maximum oxygen uptake.

Abstract: The aim of this study was to compare the results from a Cooper walk run test, a multistage shuttle run test, and a submaximal cycle test with the direct measurement of maximum oxygen uptake on a treadmill. Three predictive tests of maximum oxygen uptake-linear extrapolation of heart rate of VO2 collected from a submaximal cycle ergometer test (predictedL,)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
102
2
20

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(133 citation statements)
references
References 17 publications
9
102
2
20
Order By: Relevance
“…Furthermore, these differences allude to the notion that intensity in the MST is markedly increased compared to the gold standard test. These results are also in line with previous reports questioning metabolic (8,18,19) and performance-based (20) aspects of the classical MST.…”
Section: Results (2 Nd Heading In Importance)supporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, these differences allude to the notion that intensity in the MST is markedly increased compared to the gold standard test. These results are also in line with previous reports questioning metabolic (8,18,19) and performance-based (20) aspects of the classical MST.…”
Section: Results (2 Nd Heading In Importance)supporting
confidence: 93%
“…Lack of specificity in factors such as intensity, duration, exercise mode, technique and, particularly, musculature employed may account for significant performance differences between the proxy and the gold standard. This may explain the reduced precision frequently reported in relation to fieldtesting (3,7,8).…”
Section: Introductionmentioning
confidence: 97%
“…While estimation equation used yielded a systematic underestimation of VO 2max by 4 ml/kg/min (McCutcheon et al, 1990) in one study, no statistically significant difference was found in two other studies (Cooper, 1968;Grant S et al, 1995;McCutcheon et al, 1990). However, inexperienced runners have difficulties to find the optimal speed, and are therefore underestimated.…”
Section: Maximal Exercise Testsmentioning
confidence: 88%
“…However, inexperienced runners have difficulties to find the optimal speed, and are therefore underestimated. The multistage 20-meter shuttle run test (MST) was shown to be an accurate method to estimate VO 2max in adults in one study (r = 0.90) (Léger L & Gadoury C, 1989), whereas other studies failed to provide such strong correlations (r = 0.79 -0.86) and reported a statistically significant underestimation of VO 2max by MST (3.0 -7.5 %) (Cooper et al, 2005;Grant S et al, 1995;McNaughton L et al, 1998;Ramsbottom R et al, 1988). In children and adolescents, the correlations between MST estimates and criterion measures of VO 2max ranged between 0.71 and 0.87 (American College of Sports Medicine position stand., 1990; Boreham CAG et al, 1990;Léger L et al, 1988;Liu NYS et al, 1992).…”
Section: Maximal Exercise Testsmentioning
confidence: 99%
See 1 more Smart Citation